Disparities in experiences of emergency department care for people with a mental health condition. (March 2021) - Corscadden, Lisa; Callander, Emily J.; Topp, Stephanie M.; Watson, Diane E.
Abstract: Background: The aim of this study was to explore differences in experiences of care in Emergency Departments (EDs) for people with and without mental health conditions. Methods: Secondary analyses of a survey of 15, 995 patients from 82 EDs in New South Wales, Australia was conducted focusing on the most positive responses for 53 questions across nine dimensions of experiences. Logistic regression was used to compare experiences between people with and without a self-reported mental health condition, regardless of the reason for presentation. Results: Most patients reported positive experiences, with 60% rating care as 'very good'. However, fewer people with mental health conditions gave 'very good' ratings (52%). Their experiences were significantly less positive for 40 of 53 questions. For overall impressions of professionals, physical comfort, and continuity dimensions, experiences for those with mental health conditions were at least eight percentage points lower than those with no condition. Differences were minimal for other questions such as experiences with facilities (e.g. clean treatment areas). Conclusions: Regardless of the reason for their visit, improvements in experiences for people with mental health conditions should focus on interactions with healthcare professionals, comfort, engagement and continuity. Improving experiences of this group can help improve their outcomes of care.